Organic Management of Vegetable Diseases, Part II: Foliar Pathogens - Gary Vallad (EDIS)
The successful management of both soilborne and foliar diseases requires a multifaceted program, taking into consideration variety selection, cultural methods, biologicals, and chemical applications approved by the Organic Materials Review Institute (OMRI) and certified organic under the United States Department of Agriculture (USDA) National Organic Program (NOP). This revised 6-page review emphasizes the management of foliar disease and serves as a guide to assist growers in selecting strategies to manage disease in a sustainable system. Written by Gary Vallad and published by the Department of Plant Pathology, August 2016.